Gut Microbiota and Metabolic Dysfunction-Associated Steatotic Liver Disease - Emidio Scarpellini; Marialaura Scarcella; Jan F. Tack; Giuseppe Guido Maria Scarlata; Michela Zanetti; Ludovico Abenavoli (MDPI AG, 2024)
Background: The gut microbiota constitutes a complex microorganism community that harbors bacteria, viruses, fungi, protozoa, and archaea. The human gut bacterial microbiota has been extensively proven to participate in human metabolism, immunity, and nutrient absorption. Its imbalance, namely "dysbiosis", has been linked to disordered metabolism. Metabolic dysfunction-associated steatotic liver disease (MASLD) is one of the features of deranged human metabolism and is the leading cause of liver cirrhosis and hepatocellular carcinoma. Thus, there is a pathophysiological link between gut dysbiosis and MASLD. Aims and Methods: We aimed to review the literature data on the composition of the human bacterial gut microbiota and its dysbiosis in MASLD and describe the concept of the "gut-liver axis". Moreover, we reviewed the approaches for gut microbiota modulation in MASLD treatment. Results: There is consolidated evidence of particular gut dysbiosis associated with MASLD and its stages. The model explaining the relationship between gut microbiota and the liver has a bidirectional organization, explaining the physiopathology of MASLD. Oxidative stress is one of the keystones in the pathophysiology of MASLD and fibrosis generation. There is promising and consolidated evidence for the efficacy of pre- and probiotics in reversing gut dysbiosis in MASLD patients, with therapeutic effects. Few yet encouraging data on fecal microbiota transplantation (FMT) in MASLD are available in the literature. Conclusions: The gut dysbiosis characteristic of MASLD is a key target in its reversal and treatment via diet, pre/probiotics, and FMT treatment. Oxidative stress modulation remains a promising target for MASLD treatment, prevention, and reversal.